Validação e adaptação do sistema CR campeiro visando implementacão de projetos de agricultura de precisão no Paraguai - Pérez, Adriana Carolina Arnold (2012)
The development and economic growth in Paraguay are highly dependent on agriculture, which in recent years has undergone an expansion. The computerization of operations for managing the crops and the search for improvements based on localized management of inputs and productivity of crops that involve the use of geotechnology and global positioning systems (GPS) applied in the management of agricultural crops, the production of meshes for the realization of georeferenced soil sampling, the structuring of a digital terrain model for mapping of fertility and productivity, variable rate application of inputs, statistical analyzes and interpretation of maps, geostatistics have a promising future in rural management. With this adaptation work to Paraguay of Campeiro CR System, it seeks to meet the need of Paraguay to have software adapted to regional conditions to develop their agriculture projects in their areas of precision agriculture. Therefore, it was translated into Spanish the application of Precision Agriculture and were inserted Departments and Districts of Paraguay, as well as the bands interpretation of various attributes of soil fertility for the generation of maps of fertility according to criteria calibrated with local studies in Paraguay and has been validated tools for Precision Agriculture System through a case study conducted with a plot and a producer of Paraguay, determining spatial variability in soil attributes, and also held a tutorial of the changes affected the operation for use in country with their adaptations to the system to its application in Paraguay agriculture.